Soil Respiration in Anthropogenic Disturbed Ecosystems Compared to Deciduous Forests in the Urban Industrial Area - Bakr, Jawdat (Kurdistan Journal of Applied Research, 2024)
In urban industrial area, mining activity directly affects the dynamic of carbon, and consequently, the release of carbon dioxide (CO2) into the atmosphere. The main objective of this research is to study the impact of most important abiotic environmental factors on soil respiration in post-coalmine ecosystems. The moisture and temperature of the soil, along with CO2 outflow from the soil, were measured over three consecutive seasons, using 92 samples from coalmine heaps and 10 samples from deciduous forests in the same urban industrial region. Based on a survey of 396 species, a cluster analysis distinguished all deciduous and 22 forest plots grown on coalmine heaps from herbaceous plots from same coalmine heaps. The lowest soil respiration rate (0.62 mg CO2 per hour per square meter) was recorded in the herbaceous vegetation class on coalmine heaps, compared to (0.76 mg and 0.96 mg) from coalmine-heap forests and deciduous forests, respectively. Species richness and diversity positively affected soil respiration in heap herbaceous plots, though this effect was less pronounced in forests grown on coalmine heaps and in deciduous mixed forests. Unlike soil water content, soil temperature negatively correlated with soil respiration on coalmine heaps, diverging from the well-studied positive impact of soil temperature and respiration in deciduous mixed forests. Our spatial and temporal analyses emphasize that the water content of the substrate is the most significant abiotic element that affects the soil respiration on coalmine heaps positively during early vegetation succession.